Analisis Motivasi Hedonis Seseorang Dalam Menggunakan Media Sosial: Studi Kasus Instagram - Utama, Kharisma Adi; Nugroho, Eko; Setiawan, Noor Akhmad (Universitas Atma Jaya Yogyakarta, 2017)
Abstract.Hedonic motivation, which is often called as intrinsic motivation, plays a role in encouraging a person to use a system to meet their needs. Currently, the popular systems used in the fulfilment of one's needs are games and social media. It has been recorded that the users of Instagram, which has been ranked as the second most popular social media in America, has increased as many as 100 thousand people since the middle of 2016, with the total registered users of 600 million. This development raises a question of what drives a person to use social media. This study aims to identify factors that affect a person to use Instagram based on Hedonic Motivation System Adoption Model (HMSAM). The data were then analyzed using Partial Least Square (PLS). After the research was conducted on 245 respondents, the results prove that the motivating factors of a person to use Instagram are perceived ease of use, perceived enjoyment, and control.Keywords: hedonic motivation system adoption system (hmsam), structural equation model (sem), partial least square (pls), social media, instagram.Â Abstrak.Motivasi hedonis atau sering kali juga disebut dengan motivasi intrinsik berperan dalam mendorong seseorang untuk menggunakan suatu sistem demi memenuhi kebutuhannya. Saat ini sistem yang populer digunakan dalam pemenuhan kebutuhan seseorang tersebut adalah game dan social media. Instagram yang menduduki peringkat ke dua sebagai social media terpopuler di Amerika, tercatat mengalami pertumbuhan sebanyak 100 ribu orang sejak pertengahan 2016 dengan total pengguna yang tercatat sebanyak 600 juta orang. Melihat perkembangan tersebut memunculkan pertanyaan apa yang mendorong seseorang untuk menggunakan sosial media. Penelitian ini akan melihat faktor yang mempengaruhi seseorang menggunakan Instagram berdasarkan Hedonic Motivation System Adoption Model (HMSAM) yang kemudian dianalisis menggunakan metode Partial Least Square (PLS). Hasilnya setelah dilakukan penelitian pada 245 responden terbukti bahwa yang menjadi faktor pendorong seseorang menggunakan Instagram adalah percieve ease of use, percieved enjoyment, dan control.Kata Kunci: hedonic motivation system adoption system (hmsam), structural equation model (sem), partial least square (pls), social media, instagram.